STATISTICAL DATA AND ANALYSIS OF LITERATURE SOURCES ON PATHOPHYSIOLOGICAL MECHANISMS OF THE CROSSTALK BETWEEN ACUTE KIDNEY AND LIVER INJURY IN PRETERM NEWBORNS DURING THE EARLY NEONATAL PERIOD - О. Оболонська; Л. Вакуленко (Неонатологія, хірургія та перинатальна медицина)
Acute kidney injury (AKI) and acute liver failure (ALF) are common and potentially dangerous complications in neonates admitted to the NICU. This article reviews data on the adverse effects of AKI on liver function and the development of ALF in preterm neonates. Infants with hemodynamically significant patent ductus arteriosus (hsPDA) are highlighted.